2017
DOI: 10.1371/journal.pone.0174775
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the JMJD3 (KDM6B) histone demethylase in glioblastoma stem cells by STAT3

Abstract: The growth factor and cytokine regulated transcription factor STAT3 is required for the self-renewal of several stem cell types including tumor stem cells from glioblastoma. Here we show that STAT3 inhibition leads to the upregulation of the histone H3K27me2/3 demethylase Jmjd3 (KDM6B), which can reverse polycomb complex-mediated repression of tissue specific genes. STAT3 binds to the Jmjd3 promoter, suggesting that Jmjd3 is a direct target of STAT3. Overexpression of Jmjd3 slows glioblastoma stem cell growth … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 82 publications
(116 reference statements)
2
27
0
Order By: Relevance
“…Missense mutations and aberrant methylation of JMJD3 29 and mutation of H3K2730, 31 have been reported in GBM, indicating that JMJD3 could be involved in GBM malignancy. Furthermore, inhibition of STAT3 upregulates the expression of JMJD3 in GBM stem cells 26 . Taken together, these observations suggest that targeting the PDGFRα-STAT3 axis will induce signaling cascades to achieve anti-tumor effects in GBM.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Missense mutations and aberrant methylation of JMJD3 29 and mutation of H3K2730, 31 have been reported in GBM, indicating that JMJD3 could be involved in GBM malignancy. Furthermore, inhibition of STAT3 upregulates the expression of JMJD3 in GBM stem cells 26 . Taken together, these observations suggest that targeting the PDGFRα-STAT3 axis will induce signaling cascades to achieve anti-tumor effects in GBM.…”
Section: Introductionmentioning
confidence: 84%
“…It is involved in GBM stem cell proliferation and multipotency 25 . STAT3 also regulates the cellular epigenetic state, causing stable changes in the ability of cells to respond to stimuli in cancer development 26 . Depletion of PDGFRα attenuates GBM by modulating STAT3 and multiple oncogenic signaling pathways, 27 which suggests the presence of a PDGFRα-STAT3 regulatory axis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, combination sorafenib with quinacrine (Ha et al, 2017) and a combination of the BH3 mimic drug ABT-737 and doxorubicin (Ntziachristos et al, 2014) induced ATC cell apoptosis. Yong Sang Lee et al tested primary cells cultured from ATC patients and found that different combinations of HNHA (a histone deacetylase), lenvatinib (a fibroblast growth factor receptor inhibitor), and sorafenib (a tyrosine kinase inhibitor) were more effective than single drugs (Hjelmeland et al, 2017). However, these discoveries are still in the basic experimental stages, and there are still many problems to be solved before their actual clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously studied that H3K27 demethylase, Jmjd3 (also known as KDM6B) is responsible for the induction of most of the inflammatory genes assoiciated with LPS stimulation (De Santa et al, 2009). Recent findings also suggest that JMJD3 may be involved in acute inflammatory response and is transcriptionally regulated by STAT1 and STAT3 which are a novel mechanism critical for initiating inflammatory responses Studies have also shown that inhibition of STATs leads to the increased activity of JMJD3 (Przanowski et al, 2014; Sherry-Lynes et al, 2017). In this study, we have shown that macrophages in response to LPS stimulation, there is an increased expression of JMJD3, which causes the induction of inflammatory cyto- and chemokines as well as the induction of MAPK signaling pathway.. Acetylation of histone 3 at lysine 9 (H3K9) is associated with gene activation, whereas trimethylation of histone 3 at lysine 27 (H3K27) is associated with gene repression (Li et al, 2014; Lopez-Atalaya et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in response to inflammatory stimuli, histone lysine demethylases 6B (KDM6B) or JMJD3 is immediately induced by NF-κB in primary mouse macrophages (De Santa et al, 2007). In an early immune response, there is an increased expression of JMJD3 demethylase mRNA after inhibition of STAT3 (Sherry-Lynes et al, 2017). This increased expression of JMJD3 is responsible for the activation of inflammatory genes followed by apoptosis genes and therefore epigenetically regulates the inflammatory response (Das et al, 2012; De Santa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%